China's new Foreign Investment Law: deeper reform and more trust are needed - Yun Zheng (Columbia University, Columbia Center on Sustainable Investment (CCSI), 2019)
Against a backdrop of international economic turbulence, China passed the new Foreign Investment Law aiming to boost the trust of international investors. This Perspective highlights its three focal points: the efforts on investment facilitation, the establishment of a National Treatment and Negative List mechanism, and investment protection.
Keywords: 330